Use of closed loop system using Arduino for different parameters in farming - Saifur Rahman (Bulletin of Electrical Engineering and Informatics, 2020)
The GDP (Gross domestic product) of most countries in the world are base on the regular basis of agriculture contribution of that particular country. The current weather conditions in the world and crop loss are the main reason for its contribution to GDP. New technologies and advanced fertilizers are now used in farming though these technologies and advanced fertilizers do not reach farmers till now. In this paper, a concept for the automated watering system in agriculture is introduce which uses wireless sensors technology for the detection of moisture in the soil suitable for agriculture using a smartphone application which will play a critical role in agriculture. The automatic watering to plants using the Arduino system and android app is use. Even this application of Android will provide information to the farmers related to agriculture like costs of seeds, level of moisture required, amount of water needed, which type of soil required, forecast weather, fertilizers to be used and pesticides required.